The effects of pimpinella peregrina essential oil on anxiety and depressive-like behaviors in the scopolamine rat model of Alzheimer's disease - Akbaba, Emel Aydın; Bağcı, Eyüp; Hritcu, Lucian (My University, 2016)
Pimpinella peregrina is a member of the Apiaceae family comprising approximately 150 species distributed in the northern hemisphere. The seeds of Pimpinella species have been used in folk medicine, pharmacy and food industry, mainly due to its essential oil attributes. Neuropsychiatric symptoms such as depression, apathy, aggression, and psychosis are recognized as core features of Alzheimer’s disease. In the present study, we identified the effects of inhaled Pimpinella peregrina essential oil (1 and 3 %, for 21 continuous days) on scopolamine-induced anxiety, and depression in laboratory rats. The anxiety and depressive responses were studied by means of the elevated plusmaze and forced swimming tests. The scopolamine alone-treated rats exhibited the following: decrease of the exploratory activity, the percentage of the time spent and the number of entries in the open arm within elevated plus-maze test and decrease of swimming time and increase of immobility time within forced swimming test. Inhalation of the P. peregrina essential oil exhibited anxiolytic- and antidepressant-like effects in scopolamine-treated rats. Our results suggest that the P. peregrina essential oil inhalation ameliorates scopolamine-induced anxiety, and depression. Moreover, studies on the P. peregrina essential oil may open a new therapeutic window for the prevention of neurological abnormalities closely related to Alzheimer’s disease.
Bildiri - Yayımlanmış
Keywords: Anxiety; Depression; Pimpinella peregrina essential oil; Alzheimer’s disease